Determinants Of Online Purchase For Agroproducts Among Pasarborong.Com Customers - R. Balasingam, Ratneswary (2007)

(untitled)
Online-purchasing for agricultural products in Malaysia is not well received, despite the encouragement by the government and local vendors. This study examines the online purchasing behavior of consumers for selected agricultural products in Malaysia. The research objectives are: to document the profile of online shoppers; to document the types of products that are being purchased online; to determine the consumers behavior towards online purchasing; and to analyze factors affecting online purchases. An online survey was posted at www.geocities.com/sothy_46 . The survey focused only on online shoppers for agro products. Notice of the survey was posted through www.pasarbong.com website. The notice was also sent to the customers through www.parksononline.com.my and www.egroceries.com.my. A total of 46 participants responded. The data were analyzed using mean average, factor analysis, gap analysis and linear regression. Descriptive statistics was used to describe the respondent profile, consumer’s behavior and their beliefs of online purchasing of selected agro- products such as mean average. Factor analysis was used to uncover the dimension of the beliefs of online marketing for selected agro- products. Gap Analysis refers to the activity of studying the differences between standards and the delivery of those standards. Linear Regression model was used to predict the relationship between dependent variable of happy dealing online to independent variables used in the factor analysis. The results showed that a majority of the respondent used e-commerce to purchase services such as, providing reservation/booking online and online banking rather than to purchase goods. The survey also included questions to determine the consumers’ expectation before they first purchase online as well as their perception after they had made online purchases. In general, the experience of the respondents was not up to their expectation. Based on factor analysis, there are five factors which influenced consumer’s perception towards online marketing. They are after sales services, communication, product attribute, satisfaction and delivery. The regression analysis also found that some factors were significant in influencing the level of consumers’ satisfaction regarding online purchasing.